(untitled) (ESMAT Magazine, 2024)
Increasingly, a more efficient and suitable Public Administration is required, which uses public resources wisely, accounting for its actions to the population. In view of this, the present work aimed to analyze the importance of social Observatories in encouraging greater popular participation in management. of public administration. To achieve this, some specific objectives were defined, namely: (i) Describe popular participation in Brazil, based on the concept of democracy; (ii) List the forms of popular participation and the difficulties in implementing a more participatory management (iii) Present the functioning and activities of the Social Observatories; and, (iv) Understand the role of Social Observatories in expanding (or not) popular participation. As for the methodology, we started from a qualitative approach, we also used the descriptive-explanatory type of research and the technical procedures adopted were bibliographic and documentary. The results showed that the Social Observatories increased popular participation in the places where they were implemented, however, it is necessary to encourage greater heterogeneity among their members, in addition, the prejudiced view of party politics can be harmful in our democracy.